EMR/ESR/EPR Spectroscopy for Characterization of Nanomaterials - Shukla, Ashutosh Kumar (Advanced Structured Materials, 2017)
The subject matter of this book is the application of EMR/ESR/EPR spectroscopy for characterization of nanomaterials. Initial chapters deal with nanomaterials and their classification. Characterization of metallic nanoparticles, metal oxide nanoparticles and rare earth impurity doped nanoparticles from the (ESR) spectrum parameters are covered in the chapters that follow. A special feature of the book is EMR/ESR/EPR spectroscopic characterization of nanoparticles which are important due to their bactericidal and anticancerous properties. Strength of continuous wave (CW) is explained with the help of suitable examples. The book focuses on applications and data interpretation avoiding extensive use of mathematics so that it also caters to the need of young scientists in the life science disciplines. The book includes a comparison with other spectroscopic characterization methods so as to give an integrated approach to the reader. It will prove useful to biomedical scientists and engineers, chemists, and materials engineers in student, researcher, and practitioner positions.